Management of Sepaktakraw at Muara Enim Regency of South Sumatera - Munandar, Wahyu; Sulaiman, Sulaiman; Rahayu, Setya (Journal of Physical Education and Sports, 2021)
The background of this research is management of the Muara Enim Regency Sepaktakraw Team, whose achievements have not improved in several years. The purpose of this study is to find out the planning, organizing, actuating, and controlling of the management team for the coaching of sepaktakraw achievement in Muara Enim Regency. This research used a qualitative approach untuk menganalisis planning, organizing, actuating, and controlling. The research instrument used observation, interviews, and documentation. The research subjects are administrators, coaches, athletes, and documentation of the Muara Enim Regency Sepaktakraw Team. The data analysis technique consist of data collection, data reduction, data display, and conclusion. The results of this study are that the planning system for management, human resources, training programs, funding, and infrastructure has been structured and appropriated. The organizational system in management, training programs, funding, facilities, and infrastructure has been effective, but in human resources, there are still problems in recruiting athletes. The implementation system, management, training program, funding, and infrastructure have been implemented as they should, but in human resources, the achievement has not improved significantly. The supervisory system of management, human resources, training programs, funding, facilities, and infrastructure has been monitored regularly by the management and KONI of Muara Enim Regency. The conclusions of this study that aspects of planning and supervision are in the good category, while aspects of organizing and implementation are in the poor category, so the management has to improve the aspects that are not good to achieve great performance.